(untitled) (Foro de Educacion, 2021)
This research article pursues two objectives: (i) to explore the impact of the EU’s 2020 and Horizon 2020 Work Strategies and the IEO’s 2021 Goals in relation to the right to education and, in particular, of the immigrant population; (ii) and to develop socio-educational intervention proposals for future programmes in this area of both supranational bodies. To achieve these objectives, Comparative Education has been used as a methodology to address political, economic and socio-educational phenomena from a global perspective. This allows the similarities and differences between the two bodies to be contrasted. To this end, indicators belonging to the following categories have been used: (i) sociocultural and economic well-being; (ii) infant education; and (iii) primary and secondary or compulsory education. The results show how education policies promoted by both the OEI and the EU are having a positive impact on education. Both policies have agreed on common objectives and goals that are promoting educational improvement in the territories managed by both institutions. These results highlight the importance of supranational bodies in today’s world to alleviate social inequalities and promote equity among all people regardless of their context.